The relationship between nurses’ professional commitment and caring behaviors: A cross‐sectional study - Nimet Gokce Bekdik; Figen Turk Dudukcu (Acta Scientiarum. Health Sciences, 2025)
This study aimed to examine the relationship between nurses' professional commitment and caring behaviors. This was a cross-sectional-correlational research design. Study conducted with 293 nurses. Data were collected between January and March 2023. Ethics committee approval and informed written consent of the participant were obtained for the study. The data were collected by using the ‘Nurse Information Form’, ‘Caring Behaviours Inventory-24 (CBI-24)’ and ‘Nursing Professional Commitment Scale (NPCS)’. It was found that the mean score of the NPCS was 82.71 ± 14.306. and of the CBI-24 was 5.38 ± 0.653. Nurses’ professional commitment and caring behaviors were high. It was found that the NPCS total and subscales’ scores have positively correlations with the total and sub-scores of CBI-24. However, this relationship was weak (r = 0.421, p < .001). Professional commitment explained 17% of the variance in caring behaviors. Professional commitment and caring behaviors are at a high level in nursing. However, there is no significant relationship between nurses' professional commitment and caring behaviors. These findings may provide ideas for managers to strengthen nurses' professional commitment and increase their caring behaviors. Thus, health policies related to nurses can be developed.